Survey of attitudes, materials and methods employed in endodontic treatment by general dental practitioners in North Jordan - Al-Omari Wael M (BMC, 2004)
Abstract Background General dental practitioners provide the majority of endodontic treatment in Jordan. The aim of this study was to gather information on the methods, materials and attitudes employed in root canal treatment by dentists in North Jordan, in order to evaluate and improve the quality of current practice. Methods A questionnaire was posted to all registered general dental practitioners working in private practice in Irbid Governate in North Jordan (n = 181). The questionnaire included information on methods, materials and techniques used in endodontic treatment. Results Reply rate was 72% (n = 131). The results demonstrated that only five dentists used rubber dam occasionally and not routinely. The majority used cotton rolls for isolation solely or in combination with a high volume saliva ejector (n = 116). The most widely used irrigants were sodium hypochlorite and hydrogen peroxide, which were used by 32.9% (n = 43) and 33.6% (n = 44) of the respondents, respectively. Forty eight percent of the respondents (n = 61) used the cold lateral condensation technique for canal obturation, 31.3% (n = 41) used single cone, 9.9% (n = 13) used vertical condensation and 12.2% (n = 16) used paste or cement only for the obturation. The majority used zinc oxide eugenol as a sealer (72.5%). All, but one, respondents used hand instruments for canal preparation and the technique of choice was step back (52.7%). More than 50% (n = 70) of the dentists took one radiograph for determining the working length, whilst 22.9% (n = 30) did not take any radiograph at all. Most practitioners performed treatment in three visits for teeth with two or more root canals, and in two visits for teeth with a single root canal. Conclusions This study indicates that dentists practicing in North Jordan do not comply with international quality standards and do not use recently introduced techniques. Many clinicians never take a radiograph for determining the working length and never used rubber dam or intra-canal medicaments.